THE THEORY OF DEVELOPMENT OF SUPPORTED METAL-COMPLEX CATALYSTS - T. L. Rakitskaya (Vìsnik Odesʹkogo Nacìonalʹnogo Unìversitetu: Hìmìâ, 2015)
Some results of the investigations for the purpose of development of supported metal-complex catalysts for phosphine and carbon monoxide oxidation as well as for ozone decomposition are summarized. The activity of such catalysts has been found to depend not only on a nature of a central atom and ligands but also on a nature of supports. The theoretical model explaining mechanisms of surface complex formation taking into account the influence of physicochemical and structural-adsorption properties of the supports (SiO2, Al2O3, carbon materials, zeolites, dispersed silicas, lamellar aluminosilicates, etc.) has been proposed. For quantitative description of the support effect, such a thermodynamic parameter as the adsorbed water activity assignable with the help of water vapor adsorption isotherms has been introduced. Successive stability constants of the surface metal complexes have been calculated by the kinetic method and, hence, compositions and partial catalytic activity of the latter have been determined. Taking into account the competitive adsorption of metal ions on the supports, some schemes of formation of surface bimetallic complexes have been suggested. The compositions of the supported metal-complex catalysts have been optimized to meet requirements of their use in respirators and plants for air purification from foregoing gaseous toxicants.